Productive performance and economic analysis of intensive fattening of lambs treated with injectable zeranol and androgens under tropical conditions - Luna-Palomera, Carlos (2023)
The aim of this study was to compare the productive performance and profitability of the fattening of Kathadin male and female lambs (n=97) in confinement treated with Zeranol (ZNL), androgens (AND) and ZNL+AND under a 2x4 factorial design. The lambs treated with ZNL received 0.2 mg/kg of body weight (BW) every 28 d, those treated with AND received Nandrolone Decanoate + Trenbolone + Boldenone Undecinelate, via IM in doses of 0.3 mg/kg + 0.4 mg/kg + 0.3 mg/kg of BW, respectively, every 28 d, those treated with ZL+AND received the same doses of the mentioned drugs, while those in the control group received 0.5 mL of saline solution. Final body weight (FBW), daily weight gain (DWG), feed conversion (FC) on dry basis (DM) and wet basis (WM), and voluntary intake (VC) in DM and WM were evaluated. The FBW was different (p<0.05) between treatments in males and females. The DWG was higher (p<0.05) for females treated with AND compared to those treated with ZNL and AND+ZNL, the latter being similar to those of the control group. Females treated with AND registered a lower (p<0.05) VC compared to those treated with ZNL and AND+ZNL. Net utility, benefit: cost ratio and profitability were better in animals treated with AND. The administration of AND represents a viable alternative to make more efficient the confinement fattening systems of lambs.